Os direitos dos cotistas minoritários de Fundos de Investimento em Direitos Creditórios - Péricles Pereira Pinto (2023)
The main question that guided the research reported in this work is whether there is justification for the regulation of Investment Fund in Credit Rights (FIDC) established by the Brazilian Securities and Exchange Commission (CVM) not having attributed special protection to minority unit holders similar to that granted to minority shareholders of a public company (S.A.), such as tag along rights and public offering for the acquisition of shares in the event of deregistration and increase in shareholding. Considering that until December 22, 2022, with the issuance of CVM Resolution No. 175/2022, FIDC unit holders could only be qualified and professional investors, it was hypothesized that the lack of special protection for minority unit holders would be explained, first, by the fact that they do not qualify as shareholders since FIDCs cannot be considered as business entities for the purpose of applying the corporate legal regime. Secondly, because the CVM, through its normative competence, granted operational freedom to administrators in exchange for the establishment of a specific and complex legal regime to regulate the development of FIDC activities, including rules on the provision of information to unit holders, which were initially deemed sufficient to protect them given that as qualified investors, they would have the necessary knowledge to analyze the fund's administration and access the appropriate protection against them. To test this hypothesis, a literature review, normative analysis, and documentary analysis were conducted. The results of the study were distributed across 4 chapters, in addition to the introduction, conclusion, and references. Chapters 2 and 3 described investment funds and FIDCs, respectively, delimiting their legal nature, the applicable rules, their classification, and their administrative structure, as well as the rights of unit holders in general and minority unit holders specifically, which were further illustrated by six demonstrative figures based on CVM Resolution No. 175/2022. Chapter 4 presented the legal regime for the protection of minority shareholders in public companies, covering concepts such as majority, minority, and control power, justifications for protecting minorities, essential and individual rights of shareholders in general and minority shareholders specifically. Chapter 5 demonstrated, based on the identified differences between public companies and FIDCs, the inapplicability of Law No. 6,404/1976 to the latter, although the concepts of majority, minority, and control power are applicable to them. It was also shown that the alleged operational freedom granted to administrators may not be real, as they often remain bound by the decisions of controlling unit holders who are not always concerned with protecting the minority. The Brazilian legal system does not leave minority unit holders completely unprotected, as they can rely on the provisions of Civil Law to legally claim damages suffered as a result of potential abusive acts by administrators and controllers, as well as request their annulment. However, it was observed, especially after the issuance of CVM Resolution No. 175/2022, which allowed for common unit holders in FIDCs, that this reality puts them in a disadvantageous position when compared to minority shareholders of public companies, as they do not have the same protective mechanisms afforded to the latter. Thus, the verified hypothesis was refuted, and it was concluded that the current insufficiency of the state regulation to provide special protection to minority unit holders is only justified by historical reasons, with no logical reason that can explain treating investors with such similar legal positions differently.